Evaluating the Effects of Replacing Fish Meal with HP 300 on Nursery Pig Performance - A. M. Jones; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 350 barrows (Line 200 × 400 DNA, Columbus, NE; initially 13.6 lb) were used in a 21-d growth trial with 5 pigs per pen and 14 pens per treatment. Pigs were weaned at approximately 21-d of age, placed in nursery pens according to BW and fed a common pelleted starter diet for 3 d, at which time, pigs were weighed and then pens were blocked by BW to 1 of 5 dietary treatments in a randomized complete block design. A composite sample of fish meal and HP 300 was collected and analyzed for AA content and proximate analysis prior to formulation to determine nutrient loading values. Dietary treatments were corn-soybean-meal-based with 10% spray-dried whey and formulated to contain 1.35% standardized ileal digestible (SID) Lys and balanced on an NE basis. The 5 corn-soybean meal-based treatment diets were: 1) soybean meal control (no specialty protein products); 2) diet with 6% fish meal; 3) diet with 9.1% HP 300 replacing fish meal on a Lys basis; 4) diet with 6% HP 300 replacing fish meal on a lb/lb basis; and 5) diet with 15% HP 300 included at the expense of SBM and fish meal. All diets were fed in meal form. Overall (d 0 to 21), ADG and ADFI increased (P<0.10 and P<0.05, respectively) when pigs were fed the fish meal control diet compared to pigs fed HP 300 replacing fish meal on an SID Lys basis and 15% HP 300 diet, with pigs fed HP 300 replacing fish meal on lb/lb basis intermediate. In addition, ADG marginally decreased (P<0.10) when pigs were fed the soybean meal control diet compared with pigs fed the fish meal diet. Furthermore, pigs fed the control diet had the poorest F/G among the dietary treatments. In addition, pigs fed the fish meal diet had improved (P<0.05) final BW (d 21) compared to pigs fed the soybean meal control, HP 300 replacing fish meal on an SID Lys basis, and 15% HP 300 diet, with pigs fed diets with HP 300 replacing fish meal on a lb/lb basis intermediate. In conclusion, nursery pigs fed diets with fish meal had improved performance compared with the control diet, but 9% or greater HP 300 resulted in poorer feed intake and gain.
Keywords: fish meal; growth; HP 300; nursery pig